Evaluation of the efficacy of a locally formulated antiseptic, for the control of disease-causing microorganisms - E. Eseyin, Anthonia; O. Omale, Benjamin; D. Dodo, Juliet (International Journal of Advanced Chemistry, 2020)
An antiseptic (sample A) was locally formulated. Its efficacy on the following micro-organisms; E.Coli, staphylococcus, streptococcus and bacillus species was evaluated and compared with that of Dettol and Septol. Sample A was established to be a cheap and effective antiseptic, which is capable of competing favourably with those in the Nigerian market. The Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) indicated that Sample A had a similar efficacy with Dettol. The P-value of the MIC results for samples A, Dettol and Septol were 0.004, 0.268 and 0.080 respectively, while the P-value of the MBC results were 0.450, 0.077 and 0.043 respectively. The standard errors of the mean were 0.079, 0.072 and 0.086 for sample A, Dettol and Septol respectively.Â Â